Coolitude and Origins of Modern-day Slavery in Bahadur’s Coolie Woman - Karkee, Bhoj Raj (Ganeshman Darpan, 2026)
Through a close reading and historical review of Coolie Woman: The Odyssey of Indenture (2014) by Gaiutra Bahadur, this paper unveils how the abolition of historical slavery in 1833 in Britain paradoxically gives birth to modern-day slavery, which is considered as a serious crime against human rights, particularly labor rights as it not only does exploit labor of vulnerable individuals but also does it dehumanize them. The analysis of the text and existing research shows that labor exploitation now has not appeared all of a sudden; instead, it has developed from colonial systems of control. Using T. M. Scanlon’s deontological philosophy, especially his principle of ‘what we owe to each other,’ this paper focuses on duty, respect and human dignity as the ethical basis as the solution of the problem. Additionally, analyzing how literary texts address such ongoing social inequalities, the study attempts to add a new ethical perspective to Labor Humanities and highlights the need for a more responsible and humane approach to labor rights rather than formulating merely the sets of laws.